2015
DOI: 10.1016/j.ypmed.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and dyslipidemia in a representative population-based sample in the US

Abstract: Objective The association of food insecurity with dyslipidemia has not been firmly established. The main objective of this study was to assess whether food insecurity was associated with dyslipidemia. Method A population-based sample of 1,663 adults from the 2008–2011 Survey of the Health of Wisconsin was used. Food insecurity was defined as an affirmative response to either of the questions: 1) “In the last 12 months, have you been concerned about having enough food for you or your family?” 2) “In the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
2
22
0
2
Order By: Relevance
“…In addition, food insecurity was significantly associated with lower odds of “ideal” diet and physical activity, but had no significant relation with other factors. Our finding that food insecure individuals are less likely to have a healthy diet is consistent with previous literature (Mello et al, 2010) as well as with our own previous findings showing its association with obesity and dyslipidemia (Shin et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, food insecurity was significantly associated with lower odds of “ideal” diet and physical activity, but had no significant relation with other factors. Our finding that food insecure individuals are less likely to have a healthy diet is consistent with previous literature (Mello et al, 2010) as well as with our own previous findings showing its association with obesity and dyslipidemia (Shin et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Elucidating these social factors and their associations with people’s health represents an ongoing challenge in modern medicine which will hopefully lead to collaborative efforts and solutions that extend beyond the boundaries of traditional clinical medicine. Food security might be one of the upstream risk factors that have an effect on cardiovascular health (Abeyta et al, 2012; Seligman et al, 2007, 2010; Shin et al, 2015). Given the impact of food security on an individual’s health, health care organizations and providers, especially primary care providers, should consider screening and targeting food security as part of the standard of care, provided that this is done using a patient and family-centered approach and with consideration of available resources for referral to a social worker or social service program when appropriate (Garg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively high food prices in remote communities, combined with low incomes, cause food insecurity . In American studies, food insecurity has been associated with lower blood pressure and cholesterol levels . Even short periods of low income reduce dietary quality among remote Indigenous Australians; the most notable differences between periods of high and low money availability are in energy intake, the proportions of energy provided by fats and carbohydrates, and the ratio of sodium to potassium intake .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies address associations between food insecurity and chronic diseases such as diabetes, hypertension, and cardiovascular disease, according to self-reported illness history [4]. However, only a limited number of studies reported results of biomedical indicators of NCDs in relation to food insecurity [12]. Therefore, studies analyzing both biomedical indicators of NCDs and of measurements of food insecurity need to be undertaken.…”
Section: Introductionmentioning
confidence: 99%